PENAFSIRAN KONSTITUSI DALAM PENGUJIAN KONSTITUSIONALITAS UNDANG- UNDANG TERHADAP UNDANG- UNDANG DASAR 1945 - Tanto Lailam (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
This study is about interpretation of constitution, this study is based on the extent authority of the Constitutional Court on the interpretation of the constitution, including various verdicts that are considered as controversial.The result of the study shows that Constitution 1945 giving authority of the constitution interpretation of the Constitutional Court to evaluate the conflict of legal norm, this could be meant that the Constitutional Court is “the guardian of the constitution and the sole interpreting of constitution” and as the legitimate interpreter of the constitution. Some interesting in implementing the interpretation of the constitution as a standard toevaluate the conflict of legal norm, consists of: First, essentially, that the interpretation of the constitution is one of the ways to elaborate understandings contained in constitution text. Second, related to the independence and the freedom of judge in using an interpretation method which is not regulated by positive law, therefore the judge is free to use those interpretation methods which are appropriate with the conviction of the Justice. Justice in using the interpretation method doesn’t only have function as funnel of the act, but also has functioned as the funnel of justice since a judge is required the value of the law and the sense of justice which exists in the society (substantial justice). Refer to the theory of living constitution, therefore Constitution 1945 should be understood as a constitution which has textual and contextual dimention Third, the restriction in using the interpretation method, the constitutional judge couldn’t only focused into the originalism interpretation method which only based to original intent / the formulation of Constitution 1945 or using the other interpretations (non originalist) which oppositely those interpretation the 1945 Constitution doesn’t work according to system and/ or contended with the main idea underlying the constitution itself entirely related to the purpo se that would like to be realized. Fourth, the use of interpretation method should be able to be accounted to the publics, therefore the validity could be examined in certain cases. This is very essential to dosince Constitutional Court has an extent interpretation authority so that it could keep justice of Constitutional Court to avoid it from misuse of authority in interpreting of 1945 Constitution.